PRODUCTION AND SOME IMPORTANT PROPERTIES OF A PARTIALLY PURIFIED RENNIN-LIKE EXTRACELLULAR ENZYME FROM FUSARIUM SUBGLUTINANS (WOLLENWEBER & REINKING) NELSON et al GROWN STATICALLY (Biological Sciences - PJSIR, 2003)
Production of rennin-like extracellular enzyme was studied in static cultures of Fusarium subglutinans. Maximum production (648.5 SU/ml) was obtained at 30°C, pH value of 4.5, after 7 days of incubation where the fermentation medium was composed of 2% ,w/v, wheat flour. Production of this enzyme is assumed to be growth-associated type. Iso-propanol at the ratio of 1:1 (v/v) among different precipitating agents was selectively used to obtain partially purified enzyme that retains 28.37% of its original activity with 2.28-fold purification. Such partially purified enzyme was found active maximally at 55°C and pH value of 6.0 and was stable below 55°C for 60 min and in the pH range of3.5 to 4.5 for 60 min.